Analisis Sistem Penganggaran Berorientasi Kinerja di Pemerintahan Provinsi Jawa Barat dan DKI Jakarta - Putri Apriliani; Sonny Fransisco Siboro; Nabila Putri Untawijaya; Radiatul Adawiyah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study set out to ascertain whether the provincial governments of West Java and DKI Jakarta will adopt a performance-oriented budgeting approach. A case study using a qualitative methodology is the research technique employed. This study makes use of secondary data that is comparative-analyzed from a variety of literary sources, including government publications, news articles, and journals. The results of this exploratory inquiry demonstrate that a full paradigm shift in the issue between legislative and executive policies that result in system change is still lacking in consistency and completeness. This is because old procedures are being used, and their size and cost requirements are unclear. What is needed is an integrated monitoring system that, with the support of regional leaders and without any sectoral ego among field agents, other areas could adopt. Then, greater budget transparency must keep pushing government organizations to use faster, higher-quality electronic procurement of products and services, or e-procurement (e-proc).